Near-field photochemical and radiation-induced chemical fabrication of nanopatterns of a self-assembled silane monolayer - Fischer, Ulrich Christian; Hentschel, Carsten; Fontein, Florian; Stegemann, Linda; Hoeppener, Christiane; Fuchs, Harald; Hoeppener, Stefanie (Beilstein Journal of Nanotechnology, 2014)
A general concept for parallel near-field photochemical and radiation-induced chemical processes for the fabrication of nanopatterns of a self-assembled monolayer (SAM) of (3-aminopropyl)triethoxysilane (APTES) is explored with three different processes: 1) a near-field photochemical process by photochemical bleaching of a monomolecular layer of dye molecules chemically bound to an APTES SAM, 2) a chemical process induced by oxygen plasma etching as well as 3) a combined near-field UV-photochemical and ozone-induced chemical process, which is applied directly to an APTES SAM. All approaches employ a sandwich configuration of the surface-supported SAM, and a lithographic mask in form of gold nanostructures fabricated through colloidal sphere lithography (CL), which is either exposed to visible light, oxygen plasma or an UV–ozone atmosphere. The gold mask has the function to inhibit the photochemical reactions by highly localized near-field interactions between metal mask and SAM and to inhibit the radiation-induced chemical reactions by casting a highly localized shadow. The removal of the gold mask reveals the SAM nanopattern.
Keywords: colloid lithography; contact lithography; near-field; photochemistry; self-assembled silane monolayers